PENGAKUAN DISABILITAS TAK TAMPAK DALAM PERSPEKTIF HUKUM INDONESIA: ANALISIS PUTUSAN MAHKAMAH KONSTITUSI NOMOR 130/PUU-XXIII/2025 - Indah Dwiprigitaningtias; Santi Yulistiawaty; Firdaus M Iqbal (SINERGI : Jurnal Riset Ilmiah, 2026)
Invisible disabilities, including chronic illnesses and autoimmune conditions, have long faced limited legal recognition within Indonesia’s legal framework, particularly in employment relations. The issuance of Constitutional Court Decision Number 130/PUU-XXIII/2025 represents an important legal development in recognizing chronic illness as a potential form of disability requiring legal protection. This study aims to analyze the legal implications of the Constitutional Court’s decision on the protection of persons with invisible disabilities, particularly from the perspective of labor law. This research employs a normative juridical method using a statutory, conceptual, and case approach through the analysis of legal documents, legislation, court decisions, and relevant academic literature. The findings indicate that Constitutional Court Decision Number 130/PUU-XXIII/2025 strengthens the legal recognition of invisible disabilities by expanding the interpretation of disability beyond visible physical impairments. The decision also reinforces the principles of equality, non-discrimination, and reasonable accommodation in employment relations. However, challenges remain in practical implementation, particularly in workplace policy adaptation, employer awareness, and the provision of adequate accommodation for workers with invisible disabilities. This study concludes that the Constitutional Court’s decision constitutes an important legal instrument in promoting greater protection, legal certainty, and inclusive employment opportunities for persons with invisible disabilities in Indonesia